Wave form of motor unit action potential recorded by surface electrode during voluntary muscle contraction - Shigeru Morimoto; Shigeru Takemori (Japanese Society of Physical Fitness and Sports Medicine, 2014)
The authors detected the discrete spike potentials during contraction from surface electrodes fixed on the skin surface over the m. vastus medialis, and the spikes could always be detected with almost the same wave-form by putting the electrode on at the same point. Therefore, its electrical source in the muscle could be searched by detection of the existence of the synchronized motor unit action potential using an intramuscular electrode with surface spikes. The electrical source of the surface spikes originated from single motor unit action potential in the muscle (surface MUAP). By analyzing the surface MUAP wave-form employing both mono- and bipolar recording methods, surface MUAP allowed us to decide the position of the neuro-muscular junction and apparent path of muscle fibers on the skin surface. Marking the position of the neuro-muscular junction on the skin permits the reproducible recording of the MUAP wave-form of the same motor unit between the different experiments. Including the detection of the excitability of the spinal α-motoneuron, surface MUAP wave-form analysis would be a useful tool to investigate the structural change, such as length change of muscle fibers with the joint angle, and membrane property such as supernormal conduction velocity or supernormal phase in membrane potential at severe condition (lowered muscle temperature) in a single motor unit in situ human muscle. It emphasizes that the surface MUAP detection method is safe for a subject without any invasive damages such as an inserted electrode.